Effect of allopurinol on mortality and hospitalisations in chronic heart failure: a retrospective cohort study. Issue 3 (1st March 2002) - Struthers, A D; Donnan, P T; Lindsay, P; McNaughton, D; Broomhall, J; MacDonald, T M
Abstract : Objective: To examine whether allopurinol is associated with any alteration in mortality and hospitalisations in patients with chronic heart failure (CHF). This hypothesis is based on previous data that a high urate concentration is independently associated with mortality with a risk ratio of 4.23 in CHF. Design: Retrospective cohort study. Setting: Medicines Monitoring Unit, Ninewells Hospital, Dundee, UK. Patients: 1760 CHF patients divided into four groups: those on no allopurinol, those on long term low dose allopurinol, those on short term low dose allopurinol, and those on long term high dose allopurinol. Main outcome measures: Total mortality, cardiovascular mortality, cardiovascular hospitalisations, cardiovascular mortality or hospitalisations. Results: Long term low dose allopurinol was associated with a significant worsening in mortality over those who never received allopurinol (relative risk 2.04, 95% confidence interval (CI) 1.48 to 2.81). This may be because low dose allopurinol is insufficient to negate the adverse effect of a high urate concentration. However, long term high dose (≥ 300 mg/day) allopurinol was associated with a significantly better mortality than longstanding low dose allopurinol (relative risk 0.59, 95% CI 0.37 to 0.95). This may mean that high dose allopurinol can fully negate the adverse effect of urate and return the mortality to normal. Conclusions: Long term high dose allopurinol may be associated with a better mortality than long term low dose allopurinol in patients with CHF because of a dose related beneficial effect of allopurinol against the well described adverse effect of urate. Further work is required to substantiate or refute this finding.